2009
DOI: 10.1109/tbme.2009.2024087
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Small Bowel Slow-Wave Frequencies From Noninvasive Biomagnetic Measurements

Abstract: We report a novel method for identifying the small intestine electrical activity slow wave frequencies from noninvasive biomagnetic measurements. Superconducting QUantum Interference Device (SQUID) magnetometer measurements are pre-processed to remove baseline drift and high frequency noise. Subsequently, the underlying source signals are separated using the well-known SOBI algorithm. A simple classification scheme identifies and assigns some of the SOBI components to a section of small bowel. Slow wave freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Since respiration and other artifactual signals can dominate enteric signatures in the MENG, we used enteric SOBI components reconstructed to the sensor array to identify enteric slow waves, as outlined in figure 1 [6]. A typical bandpass filtered MENG signal during baseline is shown in figure 1a.1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since respiration and other artifactual signals can dominate enteric signatures in the MENG, we used enteric SOBI components reconstructed to the sensor array to identify enteric slow waves, as outlined in figure 1 [6]. A typical bandpass filtered MENG signal during baseline is shown in figure 1a.1.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify segments of ischemic bowel, our studies utilized CWT-filtered and SOBI-separated MENG signals. We found that Second Order Blind Identification (SOBI), a blind source separation technique, allowed the separation and identification of enteric slow wave signals from noisy, artifact-contaminated SQUID measurements [6], and to identify ischemic and normal intestinal slow wave components from raw or filtered SQUID data. We select SOBI components to retain or to eliminate based on frequency content and signal periodicity, and reconstruct the noise-reduced SQUID signal at each sensor location.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations